2012
DOI: 10.5194/acpd-12-17245-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of discrepancy between measured and modeled oxidized mercury species

Abstract: Zhang et al. (2012a), in a recent report, compared model estimates and new observations of oxidised and particulate mercury species (Hg<sup>2+</sup> and Hg<sub>p</sub>) in the Great Lakes region and found that the sum of Hg<sup>2+</sup> and Hg<sub>p</sub> varied between a factor of 2 to 10 between measurements and model. They suggested too high emission inputs and too fast oxidative conversion of Hg<sup>0</sup> to Hg<sup>2+</sup> and Hg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Recent work by Kos et al . [] found that root mean square errors and biases in modeled local mercury deposition near coal‐fired power plants decreased significantly when the emitted mercury speciation was shifted from the average speciation of 50:40:10 to 90:8:2 GEM:GOM:Hg (P) . Plume‐dilution studies [ Prestbo et al ., ] have suggested that GOM transforms to GEM in power plant plumes, presumably through reduction by another plume constituent, although contemporaneous decreases in GOM with increasing GEM were not always observed [ Prestbo et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Kos et al . [] found that root mean square errors and biases in modeled local mercury deposition near coal‐fired power plants decreased significantly when the emitted mercury speciation was shifted from the average speciation of 50:40:10 to 90:8:2 GEM:GOM:Hg (P) . Plume‐dilution studies [ Prestbo et al ., ] have suggested that GOM transforms to GEM in power plant plumes, presumably through reduction by another plume constituent, although contemporaneous decreases in GOM with increasing GEM were not always observed [ Prestbo et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recent field studies indicate that mercury in precipitation downwind of North American power plants is not elevated [Seigneur et al, 2003;Prestbo and Gay, 2009], at odds with the average quantity of oxidized (i.e., "soluble") mercury potentially emitted from these plants based on global emission inventories. Recent work by Kos et al [2012] found that root mean square errors and biases in modeled local mercury deposition near coal-fired power plants decreased significantly when the emitted mercury speciation was shifted from the average speciation of 50:40:10 to 90:8:2 GEM:GOM:Hg (P) . Plume-dilution studies [Prestbo et al, 2005] have suggested that GOM transforms to GEM in power plant plumes, presumably through reduction by another plume constituent, although contemporaneous decreases in GOM with increasing GEM were not always observed [Prestbo et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…There are still considerable knowledge gaps and uncertainties in current understanding of Hg p 1,3,22 and discrepancies have been found between observed and modeled concentrations of this species. 23 Particulate phase mercury is operationally dened as that portion that is fractionated from air onto a lter during the sampling process and is observed in both ne and coarse fractions. 2 It is likely a complex atmospheric component consisting of solid or liquid substances that can be either homogeneous or heterogeneous with respect to physical and chemical composition and shape, 21 depending on sources and atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…
particulate Hg p [8][9][10][11], Among these, elemental mercury (Hg 0 ) is the most common form found in natural gas [5,12].
Numerous techniques have been researched for eliminatingHg 0 , such as adsorption, conventional chemical oxidation, advanced oxidation, and catalytic oxidation, which
…”
mentioning
confidence: 99%
“…particulate Hg p [8][9][10][11], Among these, elemental mercury (Hg 0 ) is the most common form found in natural gas [5,12].…”
mentioning
confidence: 99%